“SLIDE-FORWARD RECESSION” : EINSTEIN’S MAIN FINDING PROVES EVEN STRONGER - Otto E. Rossler (European Scientific Journal, ESJ, 2015)
The oldest gravitational ideaof Einstein is by the use of a toy model shown to be still more powerful: It implies c-global. This new fact if true is decisive for the unification of physics. Remember how Einstein predicted gravitational redshift – the fact that our clocks tick slower than those in the satellites overhead – ? He invented the toy model of a constantly accelerating long rocketship in outer space, Jules-Verne style.